ANALISIS WACANA TEKS LAPORAN HASIL OBSERVASI SISWA - Amaliavanti, Zhafirah; Anwar, Miftahulkhairah (Universitas Hamzanwadi, 2025)
This study aims to analyze the text of students' observation report results using a discourse analysis approach. The data are in the form of five observation report texts of class X students at SMA PGRI 4 Bogor which were collected using the documentation method. This research employs a qualitative approach with discourse analysis techniques to identify text structures, sentence connectivity, the author's purpose, new information, and broader perspectives. The results of the study indicate that students have demonstrated good abilities in writing observation report texts, using clear text structures, good sentence connectivity, and the delivery of new information systematically and by the author's purpose. These findings have implications for Indonesian language teaching, particularly in enhancing students' understanding of text structure and cohesion in writing observation reports.